Bifidobacterium lactis and Lactobacillus plantarum Enhance Immune Function and Antioxidant Capacity in Cats through Modulation of the Gut Microbiota - Weiwei Wang; Hao Dong; Xiaohan Chang; Qianqian Chen; Longjiao Wang; Shuxing Chen; Lishui Chen; Ran Wang; Shaoyang Ge; Pengjie Wang; Yixuan Li; Siyuan Liu; et al. (MDPI AG, 2024)
Gastrointestinal (GI) afflictions are prevalent among the feline population, wherein the intricacies of the gut microbiome exert a profound influence on their overall health. Alterations within this microbial consortium can precipitate a cascade of physiological changes, notably in immune function and antioxidant capacity. This research investigated the impact of Bifidobacterium lactis (B. lactis) and Lactobacillus plantarum (L. plantarum) on cats' GI health, exploring the effects of probiotic supplementation on the intestinal ecosystem using 16S rRNA gene sequencing. The findings demonstrated a significant improvement in gut barrier function by reducing plasma concentrations of D-lactate (D-LA) by 30.38% and diamine oxidase (DAO) by 22.68%, while increasing the population of beneficial bacteria such as Lactobacillus. There was a notable 25% increase in immunoglobulin A (IgA) levels, evidenced by increases of 19.13% in catalase (CAT), 23.94% in superoxide dismutase (SOD), and 21.81% in glutathione peroxidase (GSH-Px). Further analysis revealed positive correlations between Lactobacillus abundance and IgA, CAT, and total antioxidant capacity (T-AOC) levels. These correlations indicate that B. lactis and L. plantarum enhance feline immune and antioxidant functions by increasing the abundance of beneficial Lactobacillus in the GI tract. These findings provide a foundation for probiotic interventions aimed at enhancing health and disease resistance in feline populations.